Quelle intégration des pays en développement dans le régime climatique ? - Pauline Lacour; Jean-Christophe Simon (Développement Durable et Territoires)
This paper focuses on the integration of developing countries in the current climate regime. It considers the implementation of the Clean Development Mechanism (CDM) to address two major issues : firstly the regional dimension of this mechanism — and particularly the leading role of Asia for CDM projects — secondly the relevance of CDM projects as part and parcel of climate policies and sustainable development strategies in Southeast Asia and China where they have been vigorously promoted by local authorities.